1999
DOI: 10.1021/jp991156s
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of N(22D) with CH3OH and Its Isotopomers

Abstract: The reaction pathways of N(2D) with methanol and its isotopomers were specified by laser pump-and-probe experiments and molecular orbital calculations. It was shown experimentally that CH3OH deactivates N(2D) efficiently to produce ground-state NH and OH radicals. The nascent state distributions of these radicals are not statistical, suggesting that the intermediate species decompose before energy randomization. A similar result was obtained for ND and OD formed in the N(2D)/CD3OD system. NH, ND, OH, and OD ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…[32][33][34] In addition, it was reported that the chains with lower M n prefer extended chain crystallization (ECC) while chains with higher M n prefer folded chain crystallization. 35,36 Considering the alternate arrangement of PLLA and PDLA chains in the lattice, SC is a typical example of intermolecular crystal nucleation and growth; 24 meanwhile, SC prefers the ECC model even with higher M n . Thus, for the PLA samples with higher M n , PLLA adopts the ECC model to a larger extent than the PLLA/PDLA blends.…”
Section: Resultsmentioning
confidence: 99%
“…[32][33][34] In addition, it was reported that the chains with lower M n prefer extended chain crystallization (ECC) while chains with higher M n prefer folded chain crystallization. 35,36 Considering the alternate arrangement of PLLA and PDLA chains in the lattice, SC is a typical example of intermolecular crystal nucleation and growth; 24 meanwhile, SC prefers the ECC model even with higher M n . Thus, for the PLA samples with higher M n , PLLA adopts the ECC model to a larger extent than the PLLA/PDLA blends.…”
Section: Resultsmentioning
confidence: 99%
“…It has been clarified that T c dependence of the radius growth rate of spherulites (G vs. T c ) shows a bellshaped curve, and that this dependence is expressed by an exponential function, including T c . 26,27 Recently, Umemoto et al 28,29 investigated G versus T c for various polymers and reported the bell-shaped G versus T c curve of poly(ethylene succinate) (PESu) that is a homologue of PBSu Miyata and Masuko 3 obtained the G versus T c of the PBSu film sample. However, no peak appeared in their G versus T c curve, because their G versus T c was obtained above 90 8C.…”
Section: Isothermal Crystallizationmentioning
confidence: 99%
“…Our earlier report demonstrated that the removal rate of a novolak photoresist increases in proportion to the H-radical density [19]. The rate of removal by H radicals at 1.0% must be much smaller than that in the pure hydrogen system because the H-radical density was reduced to less than one-half that without oxygen [9]. However, O and OH radicals are also produced with H radicals when oxygen is added.…”
Section: Resultsmentioning
confidence: 97%
“…To overcome the limitation, we examined a way of adding a trace amount of oxygen gas to the atmosphere in which H radicals are produced. According to Umemoto and Moridera [9], not only H radicals but also O and OH radicals can be produced by activating mixtures of hydrogen and oxygen on a tungsten hot-wire surfaces in the absence of photoresists. Generally speaking, OH radicals are highly reactive and thereby may improve the rate [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation